CRYPTOCURRENCIES AS A SYSTEM OF INVESTMENT PROJECTS - Сословський , Володимир; Косовський , Ігор (Socio-economic relations in the digital society, 2019)
In the article the process of development of the cryptocurrency market from the stand point of competing investment projects is considered. The main components of cryptocurrency as an investment project are considered. It is noted that the development process of the cryptocurrency market can be described as a gradual transition from a homogeneous and unidirectional to a varied and diverse system of projects. It was emphasized that cryptocurrencies as investment projects are created to meet the needs for optimizing the costs of individuals and legal entities, management and development of social projects / networks. Focused at tention is paid to the peculiarities of financing and development of these projects.